Implementation of the Transpolitan Program on Labor Absorption in Village-Owned Enterprises (BUMDES) in Muna Regency, Southeast Sulawesi Province - Herlin Rahma Fauzia; Muhammad Hanri (Publikasi Indonesia, 2024)
Transpolitan is a government program to revitalize transmigration areas with a new paradigm. One indicator of Transpolitan's success in the economic dimension is that it can optimize the role of BUMDes as a legal entity that can manage village assets, where the BUMDes workforce absorption rate is the clearest indicator for assessing BUMDes performance. Based on the results of research conducted quantitatively, it was concluded that the internal variables: transportation, population number of people, rural markets, credit facilities, retail trade, tourist attractions have a significant influence on the workforce of BUMDes. However, partially the Transpolitan variable does not have a significant effect on the absorption of BUMDes workforce in Muna Regency, Southeast Sulawesi Province. Transpolitan does not have enough of an impact because it is felt that this program has not ben massively socialized to the community so it has not aroused people's interest in transmigrating to the Mutiara Area, Muna Regency, Southeast Sulawesi Province.